Former Yugoslav Republic of Macedonia : 2017 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for the Former Yugoslav Republic of Macedonia. (IMF Staff Country Reports; Country Report ;, 2017)
This 2017 Article IV Consultation highlights slower growth in the former Yugoslav Republic of Macedonia following a solid economic recovery since the global financial crisis. Growth slowed to 2.4 percent in 2016 and contracted by 0.9 percent in the first half of 2017. Economic activity has been supported by private consumption and exports, while negative effects from prolonged political instability have restrained investment and slowed down corporate credit growth. Inflation has gradually picked up, after staying negative during the past few years. Public debt is projected to rise to 47 percent of GDP in 2017. Currently, the government is in the process of preparing the draft economic program.